THE APPLICATION OF PUBLIC BENEFIT REQUIREMENT OF CHARITABLE TRUST IN WAQF COURT JUDGMENT: A REVIEW (UUM Journal of Legal Studies, 2021)
Waqf is a form of voluntary charity and its purposes are recognised by Islamic law as religious, pious or charitable. Charitable trust is a public trust where the settlor may aim to create certain purposes. Both waqf and charitable trust share the same objective, which is for the benefit of the community at large. The objective of this article is to reveal how the requirements of “public benefit” in charitable trust are applicable to waqf cases. In determining the validity of a charitable trust, the requirement of public benefit is essential, particularly under the last three charitable purposes, namely advancement of education, advancement of religion, and other purposes beneficial to the community. Besides, the personal nexus test is applied in the case of charitable trust to ensure no personal linkage between the founder and the beneficiaries. These two elements are necessary to establish a valid charitable trust. The English court will first filter out such a case to ensure that there is no infringement of other people’s rights and exploitation of the charitable trust’s privilege. Public benefit requirement and personal test are also applicable in cases relating to waqf cases. In waqf, the Islamic law prescribes two categories, which are “Waqf Khairi” (Public waqf) and “Waqf Ahli” (Family waqf). However, family waqf is treated as “non-charitable under the influence of English law of trust” because it infringes the rule against perpetuities. The methodology used in this article is doctrinal legal research focusing on the legal principle as well as the cases of public benefit requirement, the personal nexus test, and the rule against perpetuities in charitable trust and waqf. This article found that the requirement of public benefit is applicable in public waqf, but not for family waqf. Despite that, family waqf should be maintained as it is a great channel for wealth distribution and succession planning.